Features of the Mechanism of Development and Course of Pneumonia When Exposed to Pesticides (Texas Journal of Agriculture and Biological Sciences, 2022)
The aim of presented work is to study the features of mecha- nism of the development and course of experimental pneumonia against a back- ground of body intoxication by pesticide of OPC - antio group.